ARSUKA: An Augmented Reality–Based Learning Application for Introducing Kaili Tribal Culture in Early Childhood Education - Nirmala, Besse; Agusniatih, Andi; Abdul Halim, Syafnidar; Sugiarti M. Bakri, Tri; Marwany; Annuar, Haerul; Rizal, Muh (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
This study examines the development, feasibility, and initial effectiveness of ARSUKA, an augmented reality (AR)-based learning application designed to introduce selected elements of Kaili tribal culture in early childhood education. Although AR has been widely used in early childhood settings, much of the literature has focused on cognitive or STEM-related outcomes, with more limited attention to locally grounded cultural content, particularly in Global South contexts. To address this gap, the study employed a Research and Development approach using the Hannafin and Peck model, involving needs assessment, design, and development-implementation. The application integrated Kaili cultural elements, including local language, traditional clothing, and folk songs, into an interactive AR environment supported by flashcards and puzzle-based markers. Feasibility was examined through validation by three information technology experts, three material experts, and 12 early childhood education teachers. Initial effectiveness was evaluated through a one-group pretest-posttest field trial involving 19 children aged 5-6 years in a public kindergarten in Donggala Regency, Central Sulawesi. The results showed high feasibility ratings and improvement in children’s observed acquisition of selected Kaili cultural knowledge, with mean scores increasing from 28.2 to 78.9 and an N-Gain score of 0.71. These findings suggest that AR can be designed as a culturally situated pedagogical medium rather than merely a technological add-on. The study offers a grounded example of how digital media may mediate indigenous cultural content in developmentally appropriate ways while remaining attentive to local classroom conditions. The findings should nevertheless be interpreted as evidence of initial feasibility and early effectiveness, given the small sample, single-site implementation, and short evaluation period.